2019
DOI: 10.1590/2318-0331.241920180143
|View full text |Cite
|
Sign up to set email alerts
|

Spatial discretization influence on flood modeling using unit hydrograph theory

Abstract: The Unit Hydrograph (UH) is the most popular method for flood related applications. There are several conceptual and geomorphological models based on UH and coupled with different spatial discretizations. However, there are few studies concerning the evaluation of UH models according to semi-distributed approaches. This study aimed to assess the influence of lumped and semi-distributed modeling on the applicability of Soil Conservation Service UH (SCS UH) and Clark’s Instantaneous UH (Clark’s IUH) for estimati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…The application of the MUSLE model is reiterated and subordinated to the T parameter from the probabilistic model. The tools used include QGIS for mapping works [42], and HEC-HMS for hydrometeorological simulation [27,28,43]. The factors of the MUSLE model, integrated in HEC-HMS, are estimated in a semi-distributed way in the different delimited sub-basins (Figure 3d).…”
Section: Applied Methodologymentioning
confidence: 99%
“…The application of the MUSLE model is reiterated and subordinated to the T parameter from the probabilistic model. The tools used include QGIS for mapping works [42], and HEC-HMS for hydrometeorological simulation [27,28,43]. The factors of the MUSLE model, integrated in HEC-HMS, are estimated in a semi-distributed way in the different delimited sub-basins (Figure 3d).…”
Section: Applied Methodologymentioning
confidence: 99%
“…According to the Köppen classification, the climate of the region is characterized as Cfa, with an average temperature of the warmest month exceeding 22ºC and well-distributed monthly rainfall (Alvares et al, 2014). The average annual rainfall depth in CRW is 1,367 mm (Steinmetz et al, 2019).…”
Section: Characterization Of the Study Areamentioning
confidence: 99%
“…A bunch of research found different overestimation of the peak flow with a maximum reported up to 7 times (Brunner et al, 2018;Cunha et al, 2015;Hoffmeister & Weisman, 1977;Singh et al, 2014;Steinmetz et al 2019;Tucci, 1998;Thorvat & Patel, 2016;Zakizadeh & Malekinezhad, 2015;). We highlight the definition of bold and conservative combination of parameters which produced as output, respectively, the lower and higher peak flows.…”
Section: /12mentioning
confidence: 99%
“…Considering the uncertainty of semi-distributed and concentrated modeling, Steinmetz et al (2019) explored it with SCS and Clark SUH in a 120 km 2 area basin in Brazil. The errors in the concentrated model were up to 137% and 85%, respectively for SCS and Clark methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation